Stepwise introduction of the 'Best Care Always' central-line-associated bloodstream infection prevention bundle in a network of South African hospitals. Issue 1 (September 2017) - Richards, G.A.; Brink, A.J.; Messina, A.P.; Feldman, C.; Swart, K.; van den Bergh, D.
Summary: Background: Healthcare-associated infection (HCAI) remains a major international problem. Aim: The 'Best Care Always!' (BCA) campaign was launched in South Africa to reduce preventable HCAI, including central-line-associated bloodstream infection (CLABSI). Methods: The intervention took place in 43 Netcare Private Hospitals, increasing later to 49 with 958 intensive care units (ICUs) and 439 high-care (HC) beds and 1207 ICUs and 493 HC beds, respectively. Phase 1, April 2010 to March 2011, ICU infection prevention and control (IPC) nurse-driven change: commitment from management and doctors and training of IPC nurses. Bundle compliance and infections per 1000 central-line-days were incorporated as standard IPC measures and captured monthly. Phase 2, April 2011 to March 2012, breakthrough collaborative method: multiple regional learning sessions for nursing leaders, IPC nurses and unit managers. Phase 3, April 2012 to May 2016: sustained goal-setting, benchmarks, ongoing audits. Findings: A total of 1, 119, 558 central-line-days were recorded. Bundle compliance improved significantly from a mean of 73.1% [standard deviation (SD): 11.2; range: 40.6–81.7%] in Phase 1 to a mean of 90.5% (SD: 4.7; range: 76.5–97.2%) in Phase 3 ( P = 0.0004). The CLABSI rate declined significantly from a mean of 3.55 (SD: 0.82; range: 2.54–5.78) per 1000 central-line-days in Phase 1 to a mean of 0.13 (SD: 0.09; range: 0–0.33) ( P < 0.0001). Conclusion: This intervention, the first of its kind in South Africa, through considerable motivation and education, and through competition between hospitals resulted in significant decreases in CLABSI.